2024
DOI: 10.1093/jeb/voae021
|View full text |Cite
|
Sign up to set email alerts
|

Systematic approaches to assessing high-temperature limits to fertility in animals

Amanda Bretman,
Claudia Fricke,
Julian Baur
et al.

Abstract: Critical Thermal Limits (CTLs) gauge the physiological impact of temperature on survival or critical biological function, aiding predictions of species range shifts and climatic resilience. Two recent Drosophila species studies, using similar approaches to determine temperatures that induce sterility (Thermal Fertility Limits; TFLs), reveal that TFLs are often lower than CTLs, and that TFLs better predict both current species distributions and extinction probability. Moreover, many studies show fertility is mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Sublethal effects that reduce productivity in individuals are more subtle than direct heat mortality but are essential for delimiting where populations can be maintained. In concordance with recent studies, our work highlights the importance of including thermal fertility limits in assessments of thermal stress vulnerability and in predicting species distributions (Blackburn et al, 2014;Bretman et al, 2024;Green et al, 2019;Iossa, 2019;Parratt et al, 2021;Porcelli et al, 2017;van Heerwaarden & Sgrò, 2021;Walsh et al, 2019).…”
Section: Sexsupporting
confidence: 88%
See 3 more Smart Citations
“…Sublethal effects that reduce productivity in individuals are more subtle than direct heat mortality but are essential for delimiting where populations can be maintained. In concordance with recent studies, our work highlights the importance of including thermal fertility limits in assessments of thermal stress vulnerability and in predicting species distributions (Blackburn et al, 2014;Bretman et al, 2024;Green et al, 2019;Iossa, 2019;Parratt et al, 2021;Porcelli et al, 2017;van Heerwaarden & Sgrò, 2021;Walsh et al, 2019).…”
Section: Sexsupporting
confidence: 88%
“…However, heat affects the traits differently, and reproduction of D. suzukii was more sensitive than coma and mortality. Studies across a broad range of taxa have similarly identified sublethal effects on reproduction (Bretman et al, 2024;David et al, 2005;Hurley et al, 2018;Parratt et al, 2021;Paxton et al, 2016;Porcelli et al, 2017;van Heerwaarden & Sgrò, 2021), but have largely ignored the important interaction between stress tolerance duration and stress intensity (Cook et al, 2023;Jørgensen et al, 2019Jørgensen et al, , 2021Rezende et al, 2014) as they have typically assessed the loss of fertility in response to a fixed duration of exposure. In this work, we also investigated sterility but have not presented these results as population-level sterility closely followed mortality across all temperatures; that is we could not properly distinguish between heat-induced sterility and mortality with the present experimental setup.…”
Section: Modelling Tolerance Duration Against Heat Stress Intensitymentioning
confidence: 99%
See 2 more Smart Citations